INTERNAL TRANSPARENCY OF POLITICAL PARTIES UNDER INDONESIAN POLITICAL PARTY LAW: A RULE OF LAW PERSPECTIVE ON LAW NUMBER 2 OF 2011 - Nurhidayati Arifah; Siti Hasanah; Firzhal Arzhi Jiwantara; Nurjannah Septyanun (Jurnal Ilmiah Advokasi, 2026)
Internal transparency constitutes one of the fundamental principles for strengthening democratic governance and the rule of law within political parties. Despite the enactment of Law Number 2 of 2011 concerning Political Parties, persistent concerns remain regarding the implementation of transparent decision-making, democratic political recruitment, and accountable financial management. This study aims to examine the extent to which Law Number 2 of 2011 regulates the internal transparency of political parties and evaluates its conformity with the principles of the rule of law. This research employs normative legal research using statutory and conceptual approaches. Legal materials consist of primary and secondary legal sources analyzed through qualitative legal interpretation. The findings indicate that Law Number 2 of 2011 has established a comprehensive legal framework governing internal transparency through provisions on internal decision-making, political recruitment, and financial accountability. Nevertheless, the effectiveness of these provisions remains constrained by weak institutional enforcement, limited public oversight, and political culture that has not fully embraced democratic accountability. This study contributes by proposing that strengthening internal transparency requires not only regulatory improvement but also institutional supervision and the development of democratic political culture to reinforce constitutional democracy and the rule of law in Indonesia.Keywords: Political Parties; Internal Transparency; Rule of Law; Democratic Governance; Political Party Law.